PENGEMBANGAN RUBRIK PENILAIAN LOMBA MUSABAQAH QIRAATUL KUTUB (MQK) TINGKAT KABUPATEN KAMPAR; KAJIAN KONSEPTUAL BERBASIS DOKUMEN MQK 2023 - Alfitri Alfitri (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This article aims to conceptually develop an assessment rubric model for the MQK competition at the regency level of Kampar that is aligned with principles of assessment in Arabic language education. The study is a conceptual paper based on library research and document analysis of two main sources: “Lembar Penilaian Dewan Hakim Bangkinang” and “MQK 2023 Bangkinang”. The analysis proceeds in three stages: identifying MQK assessment constructs in the official documents, critically analysing the existing instruments using the framework of analytic rubrics and performance assessment, and formulating a rubric model with clear dimensions, indicators, and operational performance level descriptors. The findings indicate that the MQK assessment system of Kampar Regency in 2023 already includes two main aspects, ṣihḥat al-qirā’ah (accuracy of recitation) and fahm al-qirā’ah (comprehension), along with subcategories that are highly relevant to the goals of Arabic language teaching. However, the absence of performance descriptors, the use of a wide unanchored scoring range, and the lack of explicit assessment of etiquette and performance are major weaknesses of the current instruments.